Genetic‐based dissection of arsenic accumulation in maize using a genome‐wide association analysis method. Issue 5 (4th December 2017) - Zhao, Zhan; Zhang, Huaisheng; Fu, Zhongjun; Chen, Hao; Lin, Yanan; Yan, Pengshuai; Li, Weihua; Xie, Huiling; Guo, Zhanyong; Zhang, Xuehai; Tang, Jihua
Summary: Understanding the mechanism of arsenic (As) accumulation in plants is important in reducing As's toxicity to plants and its potential risks to human health. Here, we performed a genome‐wide association study to dissect the genetic basis of the As contents of different maize tissues in Xixian, which was irrigated with As‐rich surface water, and Changge using an association population consisting of 230 representative maize inbred lines. Phenotypic data revealed a wide normal distribution and high repeatability for the As contents in maize tissues. The As concentrations in maize tissues followed the same trend in the two locations: kernels < axes < stems < bracts < leaves. In total, 15, 16 and 15 non‐redundant quantitative trait loci (QTLs) associated with As concentrations were identified ( P ≤ 2.04 × 10 −6 ) in five tissues from Xixian, Changge, and the combination of the locations, respectively, explaining 9.70%–24.65% of the phenotypic variation for each QTL, on average. Additionally, four QTLs [involving 15 single nucleotide polymorphisms (SNPs)] were detected in the single and the combined locations, indicating that these loci/SNPs might be stable across different environments. The candidate genes associated with these four loci were predicted. In addition, four non‐redundant QTLs (6 SNPs), including a QTL that was detected in multiple locations according to the genome‐wide association study, were found to co‐localize with four previously reported QTL intervals. These results are valuable to understand the genetic architecture of As mechanism in maize and facilitate the genetic improvement of varieties without As toxicity.